2022
DOI: 10.1111/jtxs.12663
|View full text |Cite
|
Sign up to set email alerts
|

A review on octenyl succinic anhydride modified starch‐based Pickering‐emulsion: Instabilities and ingredients interactions

Abstract: Pickering emulsions endow attractive features and a wide versatility in both food and nonfood fields. In the last decades, a noticeable interest has emerged toward the use of octenyl succinic anhydride (OSA)-starch to improve the long-term stability in such systems. In this review, instabilities were pointed out, where a new kinetic equilibrium was observed in Pickering emulsions assigned to migration and size variations of particles.These features were monitored using rheological measurements to understand mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Emulsions are one of the most widely used encapsulation systems for essential oils that increase their solubility in water, reduce volatility, and improve the stability of active substances [32]. Compared to conventional emulsions, Pickering emulsions are stabilized with solid particles that include good stability against coalescence, higher loading capacity, and lower release rate [33]. The particles used in polysaccharide-based Pickering emulsions involve starch, chitosan, β-cyclodextrin, cellulose derivatives, etc.…”
Section: Preparation and Characterization Of Emulsionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Emulsions are one of the most widely used encapsulation systems for essential oils that increase their solubility in water, reduce volatility, and improve the stability of active substances [32]. Compared to conventional emulsions, Pickering emulsions are stabilized with solid particles that include good stability against coalescence, higher loading capacity, and lower release rate [33]. The particles used in polysaccharide-based Pickering emulsions involve starch, chitosan, β-cyclodextrin, cellulose derivatives, etc.…”
Section: Preparation and Characterization Of Emulsionsmentioning
confidence: 99%
“…[34]. Starch modified with octenyl succinic anhydride is recognized as safe and approved as a food additive [35] and could be one most recommended for the preparation of Pickering emulsions [33,34].…”
Section: Preparation and Characterization Of Emulsionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies indicated that starch modified by octenyl succinic anhydride (OSA) is an ideal stabilizer for the Pickering emulsion of oil‐in‐water. [ 3,6–9 ] OSA is a dicarboxylic acid anhydride containing both hydrophilic and hydrophobic properties, which reacts with starch to produce OSA‐modified starch. The factors influencing the reaction efficiency between OSA and starch esterification are the starch pulp concentration, pH, temperature, and time course.…”
Section: Introductionmentioning
confidence: 99%